THE EARLIEST OSTRACODA RECORD FROM BRAZIL: VILA MARIA FORMATION, RIO IVAI GROUP, PARANA BASIN, CENTRAL BRAZIL - Adorno, Rodrigo Rodrigues; Do Carmo, Dermeval Aparecido; Jose Salas, Maria; Zabini, Carolina; Assine, Mario Luis [UNESP] (Soc Brasileira Paleontologia, 2016)
Two species of Ostracoda are described for the first time from the parastratotype-section of Vila Maria Formation; this section is 30 m thick, located on the northern border of the Parana Basin. The Vila Maria Formation records the Upper Ordovician-Lower Silurian boundary of the Parana Basin in Born Jardim de Goias, State of Goias, central Brazil. The new species represents the earliest Ostracoda occurrence from Brazilian strata. Delicate internal and external molds of isolated valves are abundant in the basal portion of the parastratotype-section of Vila Maria Formation. This interval comprises black shales that record post-glacial marine transgression, overlapping the Upper Ordovician glacial sequence of the Iapo Formation. The paleogeographic reconstruction indicates that deposition of the basal portion of the Vila Maria Formation took place in high-latitude, cool water conditions at the margin of Gondwana, under similar environmental conditions to the Djeffara Formation in the Ghadames Basin and the Tichitt Group in the Taoudeni Basin, both in the Northern Africa.
Keywords: Ostracoda; Ordovician; Parana Basin